LACTIC ACIDOSIS IN GOATS: PREVALENCE, INTRA-RUMINAL AND HAEMATOLOGICAL INVESTIGATIONS - A. K. Mahmood; M. S. Khan; M. A. Khan; M. A. Khan; M. Bilal; U. Farooq (Journal of Animal and Plant Sciences, 2013)
The aim of the study was to investigate the prevalence of lactic/ruminal acidosis in goats through the utilization of intra ruminal and haematological analyses as diagnostic tools. From a total study population of 2029 goats, 265 adult goats from 8 villages of Lahore, Pakistan were diagnosed for lactic acidosis on the basis of anamnesis and clinical signs. Confirmation was made through ruminal fluid analysis for its pH and defaunation. The morbidity, mortality and case fatality rates were recorded as 1.2, 0.6 and 50%, respectively. On the basis of average ruminal fluid pH, goats were assigned to four groups viz. pH 4, 5, 6 and 7. A ruminal pH of 4 was found to be lethal. Significant (P<0.05) variation was noted between all four groups. However, no seasonal influence was observed for the disease. Haematological indices were within the normal reference ranges of goats, however, marked increase in Packed Cellular Volume (PCV) and Mean Corpuscular Volume (MCV) was observed. Total leukocyte count (TLC) was also elevated than the normal range for goats. The high fatality rate of the disease envisages further monitoring of the disease through devising various biomarkers for its earlier diagnosis with emphasis on Subacute Ruminal Acidosis (SARA).
Keywords: Prevalence; ruminal acidosis; hematology; small ruminants